The gut microbiota: emerging biomarkers and potential treatments for infertility-related diseases - Wang, Min; Zheng, Lian-Wen; Ma, Shuai; Zhao, Dong-Hai; Xu, Ying (Frontiers in Cellular and Infection Microbiology, 2024)
Infertility is a disease of impaired fertility. With socioeconomic development, changes in human lifestyles, and increased environmental pollution, the problem of low human fertility has become increasingly prominent. The incidence of global infertility is increasing every year. Many factors lead to infertility, and common female factors include tubal factors, ovulation disorders, endometriosis, and immune factors. The gut microbiota is involved in many physiological processes, such as nutrient absorption, intestinal mucosal growth, glycolipid metabolism, and immune system regulation. An altered gut flora is associated with female infertility disorders such as polycystic ovary syndrome (PCOS), endometriosis (EMs), and premature ovarian failure (POF). Dysbiosis of the gut microbiota directly or indirectly contributes to the development of female infertility disorders, which also affect the homeostasis of the gut microbiota. Identifying the etiology and pathogenesis of infertility in patients is the focus of reproductive medicine physicians. We studied the developmental mechanism between the gut microbiota and PCOS, EMs, and POF from a new perspective, providing new ideas for diagnosing and treating female infertility diseases and specific reference values for eugenics.